2021
DOI: 10.3758/s13414-021-02393-z
|View full text |Cite
|
Sign up to set email alerts
|

Sounds familiar(?): Expertise with specific musical genres modulates timing perception and micro-level synchronization to auditory stimuli

Abstract: Musical expertise improves the precision of timing perception and performance – but is this expertise generic, or is it tied to the specific style(s) and genre(s) of one’s musical training? We asked expert musicians from three musical genres (folk, jazz, and EDM/hip-hop) to align click tracks and tap in synchrony with genre-specific and genre-neutral sound stimuli to determine the perceptual center (“P-center”) and variability (“beat bin”) for each group of experts. We had three stimulus categories – Organic, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 75 publications
1
18
0
1
Order By: Relevance
“…But our participants had relatively low levels of musical sophistication (measured by the Gold-MSI index, Müllensiefen et al, 2014), and several perceptual studies have reported more precise perception of timing deviations for musicians (e.g. Jones and Yee, 1997;Matthews et al, 2016;Repp, 2010) alongside perceptual centres dependent on genre-specific musical experience (Danielsen et al, 2021). Experience effects might also depend on more-naturalistic microtiming patterns, requiring more detailed probabilistic descriptions.…”
Section: Discussionmentioning
confidence: 87%
“…But our participants had relatively low levels of musical sophistication (measured by the Gold-MSI index, Müllensiefen et al, 2014), and several perceptual studies have reported more precise perception of timing deviations for musicians (e.g. Jones and Yee, 1997;Matthews et al, 2016;Repp, 2010) alongside perceptual centres dependent on genre-specific musical experience (Danielsen et al, 2021). Experience effects might also depend on more-naturalistic microtiming patterns, requiring more detailed probabilistic descriptions.…”
Section: Discussionmentioning
confidence: 87%
“…Moreover, the CA-BAT measures the ability to detect fine-grained phase offsets and this is often not necessary for many instruments in a variety of musical traditions. Indeed, the perceptual center (when a sound’s onset is perceived) has been shown to vary considerably depending on a number of musical qualities ( Danielsen et al, 2019 ), how it is measured ( London et al, 2019 ), and genre expertise ( Danielsen et al, 2022 ). It is possible that only highly trained musicians develop an enhanced beat perception ability that generalizes across sounds well enough to be observed in the beat alignment measured by the CA-BAT.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, for musically active readers, the patterns found in our study suggest that both SOIs and intensity are used to do so. Since musical training can improve and shape temporal precision ( Danielsen et al, 2022 ) and metrical discrimination ( Nave-Blodgett et al, 2021 ), it is reasonable to assume that musically active readers find it easier to quickly and accurately determine the leading meter of a poem. If their reading is oriented more toward the sound gestalt of the text and less toward comprehension, this should potentially minimize prediction errors regarding timing.…”
Section: Discussionmentioning
confidence: 99%